Photo-induced dynamic processes in perovskite solar cells: the influence of perovskite composition in the charge extraction and the carrier recombination. Issue 13 (20th March 2018) - Montcada, Núria F.; Méndez, Maria; Cho, Kyung Taek; Nazeeruddin, Mohammad Khaja; Palomares, Emilio
Abstract : We describe how the use of photo-induced charge extraction technique can be useful to study and understand the relationship between perovskite composition, ion reorganization process and solar cell efficiency. Abstract : We describe in this work how the use of the photo-induced charge extraction (PICE) technique can be useful to study and understand the relationship between perovskite composition, ion migration processes and solar cell performance. Our results show that varying the organic cation and halide composition in perovskite crystals has an effect on the charge extraction process, which is related to the differences in the ion migration process occurring during light irradiation. Moreover, we do also observe that different perovskites also show differences in interfacial carrier recombination kinetics under operando conditions but the dynamics are too fast to be influenced by the ion migration.